2009
DOI: 10.1590/s1020-49892009000100007
|View full text |Cite
|
Sign up to set email alerts
|

Screening for lead exposure in children in Belize

Abstract: These data indicate that children in Belize are being exposed to lead and suggest that this pilot study be followed up with a comprehensive study with a larger sample and correlation of the findings to socioeconomic characteristics, to children's behavior, and to the home and school environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
3
1
1
Order By: Relevance
“…The BLL mean (7.9 ± 5.4 µg/dL) determined in the children participating in this research by LCS was 38 % higher than that found in Belizean children of 4.9 ± 2.5 µg/dL (Charalambous et al 2009). The BLL in the general population frequently is lower than that found in populations with environmental or occupational exposure to this compound.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…The BLL mean (7.9 ± 5.4 µg/dL) determined in the children participating in this research by LCS was 38 % higher than that found in Belizean children of 4.9 ± 2.5 µg/dL (Charalambous et al 2009). The BLL in the general population frequently is lower than that found in populations with environmental or occupational exposure to this compound.…”
Section: Discussioncontrasting
confidence: 61%
“…In a population exposed to emissions from a lead smelter and artisanal battery recycling plant it was found that 80 % of children have concentrations higher than 10 µg/dL (Charalambous et al 2009), in the same industrial sector, but in the city of Avalos, Chihuahua, this percentage was 34 % (Flores-Ramírez et al 2012). Twenty and twelve percent of children living near a metallurgical (copper smelting and electrolytic zinc smelting) and mining-metallurgical area, as well as 15 % of potter children in the Trinidad Tenexyecac, Tlaxcala, were assigned to the category II of the Mexican regulation (Flores-Ramírez et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to age, studies have shown that younger children are at greater risk of presenting elevated BLL [9,10,13], especially infants aged <2 years, probably related to the infants' close contact with the environment, hand-to-mouth contact and predisposition to pica [4,14]. However, in this respect, Charalambous et al [38] found no significant differences. Our own bivariate analysis showed that the group aged 12-16 years had the highest BLL and the highest prevalence of toxic BLL (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies, too, have associated low socioeconomic status with jobs presenting an increased risk of lead exposure [41]. Moreover, undocumented immigrants have more difficulty choosing work, and this factor can push them towards occupations where the exposure to lead may be greater [12], working as mechanics, possibly handling lead batteries, or in contact with lead-contaminated soil or materials [38]. The lead that is handled at work may subsequently be transported into the worker's home, exposing family members to the same risk [9].…”
Section: Discussionmentioning
confidence: 99%
“…Un efecto poco explorado, en relación con la exposición a niveles de plomo en sangre bajo 10 µg/dl, es el rendimiento escolar, que se ha estudiado a través de las calificaciones, entrevistas con padres o apoderados e informes de conducta entregados por las escuelas (Leal-Escalante et al, 2007, Charalambous et al, 2009, Chiodo et al, 2007, Wang et al, 2002.…”
Section: Pág 27unclassified